Inovação aberta e gestão do conhecimento: como as empresas alcançam resultados de inovação - Tonelli, Adriano Olímpio (2017)
Knowledge management (KM), organizational capacity to create, retain and share knowledge, involves an important mechanism to generate innovation for organizations. Open innovation, term used to designate the intentional use of knowledge flows for, inbound, and from, outbound, organizational boundaries, is an alternative for organizations to, respectively, speed internal innovations and seek new paths for external technology transference. However, in literature, there is little understanding on how KM and open innovation can integrate in order to generate results associated to innovation. This work was conducted with the objective of proposing and testing an explanatory model that integrates knowledge management and open innovation. From this integration, the model contemplates three types of strategies for generating internal innovation and external technology transfer results: (i) internal, based on KM; (ii) external, based on open innovation and (iii) hybrid, defined from combinations between KM and open innovations. The model was tested using the Partial Least Squares (PLS) on a sample of 228 Brazilian organizations from the software sector. The results showed that: (i) internal strategies are the most important for generating internal innovation results; (ii) external strategies are not effective for directly generating internal innovation; (iii) hybrid strategies are relevant for treating turbulences and uncertainties and for external technology transfer. The results bring theoretical contributions to the study fields on knowledge management and innovation management, providing a new view for integrating these two perspectives for explaining different results associated to innovation.